Pembuatan Nugget Dari Biji Nangka Upaya Mengoptimalkan Sumber Daya Masyarakat Desa Kualu Nenas - Nasution, Hasmalina; Putri, Rahmayani Indah; Hidayati, Retno; Prasetya, Prasetya; Perdana, Fitra; Syafri, Rahmadini; Syahri, Jufrizal; Hilma, Rahmiwati; Siregar, srihilma; Ramadhanti, Aulia Rizki (Lembaga Dongan Dosen, 2023)
Kualu Nenas Village is a village that produces quite a lot of jackfruit flesh in the form of chips for sale. UMKM that process jackfruit as the main ingredient will have an impact on the amount of easily damaged organic solid waste from the jackfruit itself, such as jackfruit seeds. However, in processing jackfruit seeds are more often just boiled or fried as a snack. One way to process jackfruit seed waste is to make nuggets. Socialization and nugget making training activities were carried out in Kualu Nenas Village with the PPK Ormawa HIMAKI team. The aim of this activity is to increase knowledge and skills for the people of Kualu Nenas Village in processing waste, optimizing natural resources, and improving the community's economy by selling jackfruit seed nuggets. The activity began with a presentation through socialization of material about waste jackfruit seeds and nuggets in general, then continued with practical training in making nuggets from waste jackfruit seeds. The results obtained from this community service activity are that the community can understand the techniques for processing jackfruit seed waste into nuggets well as shown by the achievement percentage ≤ 74%.